Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5cc06453h
|View full text |Cite
|
Sign up to set email alerts
|

Pre-concentration and energy transfer enable the efficient luminescence sensing of transition metal ions by metal–organic frameworks

Abstract: The 2,2'-bipyridyl moieties lining the channels of two designer metal-organic frameworks (MOFs), UiO-bpydc and Eu-bpydc (bpydc is 2,2'-bipyridine 5,5'-dicarboxylic acid), recognize and pre-concentrate metal ion analytes and, in the case of Eu-bpydc, transfer energy to the Eu(3+) centers, to provide highly sensitive luminescence sensors for transition metal ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 30 publications
(32 reference statements)
0
37
0
Order By: Relevance
“…UiO‐67(bipy) has been investigated for alternative applications including luminescent sensing of transition metal ions, where the MOF acts as both the chelator and the fluorescence reporter . Of the range of transition metal ions investigated during the study, Mn II , Fe II , Fe III , Cd II , Co II , Cu II , Ni II and Zn II were all found to quench the MOF's intrinsic luminescence, with the most sensitive detection observed for Fe III , at a detection limit of 3.2 parts per billion.…”
Section: Postsynthetic Metalationmentioning
confidence: 99%
“…UiO‐67(bipy) has been investigated for alternative applications including luminescent sensing of transition metal ions, where the MOF acts as both the chelator and the fluorescence reporter . Of the range of transition metal ions investigated during the study, Mn II , Fe II , Fe III , Cd II , Co II , Cu II , Ni II and Zn II were all found to quench the MOF's intrinsic luminescence, with the most sensitive detection observed for Fe III , at a detection limit of 3.2 parts per billion.…”
Section: Postsynthetic Metalationmentioning
confidence: 99%
“…Although coordination interaction between Ag + and 2,2′‐bipyridine moieties exists (XPS spectra in Figure S6 in the Supporting Information), the quenching sites are not the coordination bond, according to the fluorescence lifetime study (Figure S8, Supporting Information). These two mechanisms can be differentiated by the fluorescence lifetime study: dynamic quenching will show a comparable decrease in lifetime, while static quenching does not change the lifetime . Therefore, Ag + ‐induced fluorescence quenching of Eu(III)@UMOFs is dynamic quenching, which results from encounter of Ag + and the excited state of ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Such a strong and local ligand-analyte binding effectively concentrates the analyte within an extremely small volume of the gel for as high as 10 9 folds (i.e., concentrating an analyte droplet of 10 µL or 1 × 10 10 µm 3 into a 1.7 µm 3 volume). Compared to other high-performance sensors based on rigid porous carrier such as metal-organic framework, [13] the unique large volumetric shrinkage (≈10%) of the soft gel network further enhances the magnitude of this local concentrating effect. As a result of the ligand-analyte binding, the gel locally contracts or swells, depending on the ligand-to-analyte ratio, which leads to local thickness change.…”
Section: Hydrogelsmentioning
confidence: 99%